Petrography of the Deosai volcanics N. Pakistan - Hamidullah, Syed; Jan, M. Qasim; Khan, Barkatullah (Journal of Himalayan Earth Sciences, 1992)
The western extension of the Dras volcanics in the Deosai plateau is made up of agglomerates and tuffs together with flows comprising basalt, andesite and some rhyolite. The flows appear to have evolved from a basaltic magma, with opaque oxide, clinopyroxene, hornblende and plagioclase, respectively appearing on the liquidus. These have been metamorphosed under green-schist facies conditions and may contain abundant epidote, chlorite and secondary amphibole. An 40Ar/39Ar age of 125.4 ± 6 Ma on hornblende phenocrysts in an andesite is in agreement with the Late Jurassic to Cretaceous age of the Dras volcanics.